2016
DOI: 10.1515/ppb-2016-0051
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship of emotional intelligence with mental health status in polish unemployed persons – differences between men and women

Abstract: This study investigates the relationship between EI and the state of mental health of unemployed persons. Gender differences were also identified in terms of mental health and its correlation with EI. A sample of 160 Polish unemployed persons aged 35 to 45 years filled in self-descriptive measures of EI and mental health. Significant gender differences were found - unemployed women were characterised by a greater intensity of mental health disorders than unemployed men. EI was negatively correlated with mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Specifically, there is general consensus, across different clinical and nonclinical samples and using different methodological approaches to EI measurement, that EI is negatively related to depression, suggesting that EI might be a protective factor against depression [ 13 , 23 ]. Specifically, recent research on unemployment and health has shown that EI plays a key role in reducing negative psychological symptoms associated with unemployment, including depression, and in boosting well-being [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, there is general consensus, across different clinical and nonclinical samples and using different methodological approaches to EI measurement, that EI is negatively related to depression, suggesting that EI might be a protective factor against depression [ 13 , 23 ]. Specifically, recent research on unemployment and health has shown that EI plays a key role in reducing negative psychological symptoms associated with unemployment, including depression, and in boosting well-being [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, EI might be crucial in explaining individual differences in managing negative emotions related to chronic unemployment. For example, recent research indicates that EI plays a key role in reducing psychological symptoms associated with unemployment, such as depression and anxiety, and boosts well-being (Extremera and Rey, 2016; Hodzic et al, 2015a; Knopp, 2016; Peláez-Fernández et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A well-motivated employee is an important asset in an organisation because of job outcomes. Emotional intelligence is thought to play a significant role in the motivation of employees' actions and behaviours (Young et al, 1997;Noorbakhsh, Besharat & Zarei, 2010;Plaude & Rascevska, 2011;Knopp, 2016;Magnano, Craparo & Paolillo, 2016). According to researchers such as Pope and Singer (1990), and Salovey and Mayer (1990), emotional intelligence is a kind of relational intelligence that entails the capability to track the emotions and feelings of others as well as the individual own emotions and feelings, and further leads an individual to think and act.…”
Section: Introductionmentioning
confidence: 99%